Differential diagnosis of a scrotal mass. Issue 1 (January 2014) - Bromby, Adam; Cresswell, Joanne
Abstract The authors discuss the various presentations of scrotal swellings, explaining how a careful clinical assessment and use of ultrasound can aid diagnosis and management of this common problem. Copyright © 2014 John Wiley & Sons